How similar are you to the fruit fly? Drosophila melanogaster as model for studying human diseases - Ferrero, Paola Viviana (2021)
Drosophila melanogaster is a holometabolous insect with a short life cycle. Its genome is completely sequenced, and it is easy to grow in the laboratory. More than 120 years of history using Drosophila have allowed us to clarify the inheritance laws and to understand cellular and molecular mechanisms of mammalian development in this model. Approximately 75% of the genes responsible for several human diseases have homologs in the fruit fly. This work addresses some advantages of using this model organism for human pathophysiology studies. Neurodegenerative disorders, heart disease, and nephropathies can be modeled in transgenic organisms, affecting the homologous gene or expressing the human sequences. It is also possible to study multi-organ pathophysiological conditions such as aging, diabetes, and cancer. In addition, Drosophila has been used to explore substances of human consumption such as cocaine, methamphetamine, caffeine, alcohol, tobacco, and cannabinoids. Finally, the versatility of this organism and the knowledge of its genome have made it possible to undertake large-scale pharmacological studies to learn about the interactions between substances and genes, to find new drugs.